2021
DOI: 10.15420/usc.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Door-to-balloon Time for ST-elevation MI in the Coronavirus Disease 2019 Era

Abstract: In patients presenting with ST-elevation MI, prompt primary coronary intervention is the preferred treatment modality. Several studies have described improved outcomes in patients with door-to-balloon (D2B) and symptom onset-to-balloon (OTB) times of less than 2 hours, but the specific implications of the coronavirus disease 2019 (COVID-19) pandemic on D2B and OTB times are not well-known. This review aims to evaluate the impact of COVID-19 on D2B time and elucidate both the factors that delay D2B time and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…During the COVID-19 pandemic, the American College of Cardiology, American College of Emergency Physicians, and Society for Cardiovascular Angiography and Interventions still advocated for PCI as the standard of care for STEMI, performed by expert teams wearing personal protective equipment in dedicated cath labs in hospitals with PCI capabilities [ 30 ]. The effects of the COVID-19 pandemic on DTB times in STEMI patients have been investigated [ 23 , 24 , 25 , 26 , 27 , 31 ]. A systematic review and meta-analysis conducted by Chew et al showed that a significant delay in DTB time was observed during the pandemic, particularly in low-to-middle-income eastern countries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, the American College of Cardiology, American College of Emergency Physicians, and Society for Cardiovascular Angiography and Interventions still advocated for PCI as the standard of care for STEMI, performed by expert teams wearing personal protective equipment in dedicated cath labs in hospitals with PCI capabilities [ 30 ]. The effects of the COVID-19 pandemic on DTB times in STEMI patients have been investigated [ 23 , 24 , 25 , 26 , 27 , 31 ]. A systematic review and meta-analysis conducted by Chew et al showed that a significant delay in DTB time was observed during the pandemic, particularly in low-to-middle-income eastern countries [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the net effects of temporal differences (daytime vs. evening vs. nighttime) on a delay in DTB time, logistic regression with a forward-selection Wald test was performed with adjustments for the associated predictors and variables with a p -value < 0.1, as derived from the univariate analysis. The adjusted variables included age [ 10 , 20 , 21 ], sex [ 10 , 20 , 22 ], visits on the weekends [ 11 , 12 , 13 , 15 ], visits during the COVID-19 pandemic [ 23 , 24 , 25 , 26 , 27 ], triage levels [ 7 , 28 ], and the region of infarction [ 10 ]. Additionally, logistic regression with adjustments for the aforementioned variables was carried out for secondary outcomes to determine which period within DTB time was primarily affected by ED arrival time.…”
Section: Methodsmentioning
confidence: 99%